The emergence of anti-environmentalism in the United States in light of the contemporary democratic crisis - Pedro Henrique Ramos Prado Vasques (Ambiente & Sociedade)
Abstract It is possible to attribute several meanings to anti-environmentalism throughout its historical trajectory. Although protecting the particularities of specific cases, the present text argues that this antagonism observed in the 21st century would not appear as a change in public administration styles, but as a rupture vector. The Study analyzed the United States case to develop the aforementioned hypothesis. The analysis took the federal administration’s performance at domestic and international level, between 1970 and 2021, as an analytical axis, which was focused on republican administrations, based on documentary analysis. Reflections carried out over the study enabled perceiving the anti-environmentalism issue as an aspect of the contemporary crisis of Western liberal democracies. Therefore, in conclusion, the conditions allowing environmentalism to exist as such, rather than environmentalism itself, are the factors at stake in this disruptive attempt.